Social Studies Learning Innovation According to Appreciative Inquiry Approach for Develop Creative Thinking Competencies in the Existence of Local Cultural Values of Secondary School Students - Kunmanee, Patcharapa; Mangkhang, Charin (Journal of Humanities and Social Sciences Thonburi University, 2022)
The purposes of this article are to create a Social Studies Learning Innovation and to evaluate the learning units based on Appreciative Inquiry Approach to develop creative thinking competencies in terms of the existence of local cultural values for secondary school students. A research method aims to create a instructional model based by reviewing the paper and related research. It is then created into a conceptual framework and reviewed by five experts to evaluate the suitability of the design’s components and content. The finding of the research revealed that consists of two components: 1) concepts, meanings, conceptual learning, and application are all principles to consider when creating an instructional model based on Appreciative Inquiry Approach and 2) learning to develop creative thinking competencies in terms of the existence of local cultural values includes Appreciative Inquiry Approach Learning Units. It can be concluded that the creation of an instructional model can be used as a concrete innovation in learning through educational institutions.